Mitigating Swelling of the Solid Electrolyte Interphase using an Inorganic Anion Switch for Low‐temperature Lithium‐ion Batteries - Liang, Jia‐Yan; Zhang, Yanyan; Xin, Sen; Tan, Shuang‐Jie; Meng, Xin‐Hai; Wang, Wen‐Peng; Shi, Ji‐Lei; Wang, Zhen‐Bo; Wang, Fuyi; Wan, Li‐Jun; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2023)
In overcoming the Li+ desolvation barrier for low‐temperature battery operation, a weakly‐solvated electrolyte based on carboxylate solvent has shown promises. In case of an organic‐anion‐enriched primary solvation sheath (PSS), we found that the electrolyte tends to form a highly swollen, unstable solid electrolyte interphase (SEI) that shows a high permeability to the electrolyte components, accounting for quickly declined electrochemical performance of graphite‐based anode. Here we proposed a facile strategy to tune the swelling property of SEI by introducing an inorganic anion switch into the PSS, via LiDFP co‐solute method. By forming a low‐swelling, Li3PO4‐rich SEI, the electrolyte‐consuming parasitic reactions and solvent co‐intercalation at graphite‐electrolyte interface are suppressed, which contributes to efficient Li+ transport, reversible Li+ (de)intercalation and stable structural evolution of graphite anode in high‐energy Li‐ion batteries at a low temperature of −20 °C. Inclusion of difluorophosphate anion in the primary solvation sheath of a weakly‐solvated electrolyte helps to switch the swelling properties of solid electrolyte interphase (SEI) on a graphite (Gr) composite anode. By forming a low‐swelling, Li3PO4‐enriched SEI, reversible Li+ (de)intercalation was enabled at a stable Gr‐electrolyte interface, contributing to improved low‐temperature electrochemical performance of a Li‐ion battery.